Alternatif Strategi Bauran Pemasaran 7P Museum Batik Yogyakarta - Hanggraito, Ahmadintya Anggit; Wiratama, Ahmad Sidiq; Saifuddien, Rahma Amalia (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2020)
Yogyakarta Batik Museum is one of the tourist destinations where as batik as major attraction. The museum is not only being a place of batik storage collections, but also offer hotels, batik shops and training of classic batik production. This study aims to provide Alternatives on marketing strategies through 7P marketing mix analysis in Yogyakarta Batik Museum. The type of research used is descriptive qualitative. Primary and secondary data are used in analyzing the 7P marketing mix at the Yogyakarta Batik Museum. The data was obtained that concerns on products, prices, places, promotions, physical evidence, people and processes in implementation the marketing strategy of the Yogyakarta Batik Museum. The results of this study are recommended alternative marketing strategies for the Yogyakarta Batik Museum. These alternative strategies are Strengthening historical and cultural values as the identity of products from batik in Yogyakarta batik museum, Differentiation of ticketing prices for tourists, Optimization of online strength through social media, and Optimization of tasks and jobs in Human Resources.